Evaluation of prickly (opuntia ficus-indica) fruit on growth performance, blood indices and methane emissions by yearling male Pedi goats - Magonyane, Travor Tshepiso (My University, 2024)
The study was conducted to determine the effect of prickly pear (Opuntia ficus-indica) in diets on growth performance, blood indices, and methane emissions of yearling male Pedi goats. A total number of 24 Pedi goats were randomly assigned to 4 treatments in a completely randomized design, replicated six times with 1 goat per replicate. All goats were of the same age group and were sourced from University of Limpopo Experimental Farm. Prickly pear inclusion levels were at 0,10, 20 or 30%. The experiment was conducted for 28 days (21-day preliminary and 7-day collection periods). Methane emission by goats was measured daily during the collection period and measurements were done using a hand-held methane detector. Goat blood samples were collected prior the commencement of the experiment and towards the end of the experiment. To assess blood parameters (lymphocytes, monocytes, neutrophils, eosinophils, and basophils), blood samples (5 ml) were collected using hypodermic needles to draw blood from every goat through the jugular vein into marked sterile tubes which contained ethylenediaminetetraacetic acid (EDTA), which served as an anticoagulant. The data collected were subjected to analysis of variance using Statistical Analysis System Software. Prickly pear meal inclusion level on diet had an effect (P<0.05) on DM, OM, Ash, CP, ADF, NDF, and EE intakes of yearling male Pedi goats. Male Pedi goats fed diets having 10 and 20% had higher (P<0.05) DM, OM, Ash, CP, ADF, NDF, and EE intakes than those on a diet having a 0 and 30% Prickly pear meal inclusion levels. Male Pedi goats fed diets having 10 and 30% Prickly pear meal inclusion levels had higher (P<0.05) DM and OM digestibility values than those fed diets having 0 and 20 % Prickly pear inclusion levels. Prickly pear inclusion level in a diet had no significant effect (P>0.05) on the initial live weight, feed conversion ratios and water intake of goats. However, Prickly pear inclusion level in a diet showed a significant effect (P<0.05) on final live weight, average daily gain (ADG) and feed intake of male Pedi goats. Prickly pear inclusion level in a diet had an effect (p<0.05) on methane emissions by Male Pedi goats. Male Pedi goats on a diet having a 0% Prickly pear meal inclusion level had higher (P<0.05) methane emissions than those on a diet composed of 0, 20 and 30% Prickly pear inclusion levels. Blood parameters of male Pedi goats revealed significant differences between the treatments at the beginning of the experiment. At the end of the trial, Prickly pear inclusion in the diet showed significant effect (p<0.05) on eosinophils of male Pedi goats. A positive relationship was observed between Prickly pear meal inclusion level xii and monocytes (r2=0.340), eosinophils (r2=0.452) and basophils (r2=0.303) of male Pedi goats. Nutrient intake, digestibility, feed conversion ratio and blood profiles of Pedi goats in the present study were optimized at different inclusion levels of Prickly pear meals. Although, Prickly pear meal reduced methane emission, optimal reduction in methane emission was not determined. Further validation is required to determine Prickly pear inclusion levels for optimal methane production and emission by goats. It was concluded that indigenous Pedi goat optimal productivity responses to Prickly pear meal inclusion were variable, depending on the production parameter in question.
Thesis (M.Sc. Agriculture (Animal Production)) -- University of Limpopo, 2024
Keywords: Prickly pear; Yearling goats; Feed intake; Digestibility; Growth performance; Prickly pear -- South Africa; Goats -- South Africa; Goats -- Feeding and feeds